Molecular and Biochemical Analysis of Duplicated Cytosolic CuZn Superoxide Dismutases of Rice and in silico Analysis in Plants - Sanyal, Ravi Prakash; Prashar, Vishal; Jawali, Narendra; Sunkar, Ramanjulu; Misra, Hari Sharan; Saini, Ajay (Frontiers in Plant Science, 2022)
Superoxide dismutases (SODs, EC 1.15.1.1) are ubiquitous antioxidant metalloenzymes important for oxidative stress tolerance and cellular redox environment. Multiple factors have contributed towards the origin and diversity of SOD isoforms among different organisms. In plants, the genome duplication events, responsible for generation of multiple gene copies/gene families, have also contributed towards the SOD diversity. However, importance of such molecular events on characteristics of SODs has not been studied well. The present study investigated the effects of divergence on important characteristics of two block-duplicated rice cytosolic CuZn SODs (OsCSD1, OsCSD4), along with in silico assessment of similar events in other plants. Analysis revealed heterogeneity in gene length, regulatory regions, untranslated regions (UTRs), and coding regions of two OsCSDs. Inconsistency in the database-predicted OsCSD1 gene structure was also identified and validated experimentally. Transcript analysis showed difference in the basal levels and stress responsiveness of OsCSD1 and OsCSD4, and indicated presence of two transcription start sites in the OsCSD1. At amino acid level, the two OsCSDs, showed differences at 18 sites, however both exist as homodimer, displayed typical CuZn SOD characteristics, and enhanced the oxidative stress tolerance of E. coli cells. However, OsCSD4 showed higher specific activity as well as stability. Comparison of the two OsCSDs with reported thermostable CSDs from other plants identified regions likely to be associated with the stability, while homology modeling and superposition highlighted structural differences. The two OsCSDs displayed heteromeric interaction capability and forms an enzymatically active heterodimer (OsCSD1:OsCSD4) on co-expression, which may have significance as both are cytosolic. In silico analysis of 74 plant genomes revealed the prevalence of block duplications for multiple CSD copies (mostly cytosolic). The divergence and clustering analysis of CSDs suggested possibility of an ancestral duplication event in monocots. Conserved SOD features indicating retention of SOD function among CSD-duplicates were evident in few monocots and dicots. In most other species, the CSD copies lacked critical features and may not harbor SOD function, however other feature-associated functions or novel functions might be present. These aspects of divergent CSD copies encoding co-localized CSDs may have implications in plant SOD functions in cytosol and other organelles.